Effect of quenching temperature on the microstructure and mechanical properties of 30MnBNbV hot stamping steel. (13th September 2019) - Chen, Weijian; Wang, Shuai; Zhao, Zhengzhi; Liang, Jiangtao; Guo, Jie
Abstract: A low carbon steel microalloyed with Nb-V subjected to hot stamping process, then quenching to different temperatures (30 °C, 230 °C, 300 °C) followed by air cooling to room temperature was investigated. The method in this article was significantly simplified compared with the conventional quenching & tempering (QT) process. The results shown that the best comprehensive mechanical properties could be obtained at 230 °C. The yield strength (YS) and ultimate tensile strength (UTS) were 1128.8 MPa and 1768.8 MPa respectively, and the total elongation was 8.8% without much compromise. The excellent properties were attributed to a multi-morphology microstructure which consisted of large amount of martensite (block fresh martensite and lath tempered martensite) and trace carbon-enriched retained austenite. In addition, the recovery of block fresh martensite (FM) and decomposition of unstable austenite were discussed during air cooling to room temperature process.